Case report diabetic foot infection wagner grader 4 pada digiti 1 pedis dextra disertai osteomielitis phalanx distal digiti 1 pedis dextra dan peripheral arterial disease ringan - Khusnulilda Khusnulilda; Berry Erida Hasbi; Hasan Hasan (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Gangrene and osteomyelitis are serious complications of chronic lower extremity wounds that can lead to progressive tissue destruction, increase the risk of amputation, and worsen clinical outcomes. Early diagnosis and appropriate management are essential to control infection and prevent further complications. Case Presentation: A 68-year-old man presented with a wound on his right great toe that had persisted for two months and worsened over the preceding two weeks. Physical examination revealed a gangrenous ulcer of the right hallux accompanied by edema, pain, blackish discoloration, and purulent discharge. Laboratory investigations showed leukocytosis, anemia, thrombocytopenia, and hypoalbuminemia, while an ankle-brachial index of 0.84 indicated mild peripheral arterial disease. Plain radiography of the right foot demonstrated osteolysis of the distal phalanx consistent with osteomyelitis. Based on the clinical, laboratory, and radiological findings, the patient was diagnosed with gangrene of the right hallux complicated by osteomyelitis. Management included antibiotic therapy, correction of nutritional and electrolyte abnormalities, and right hallux amputation with debridement of necrotic tissue. Postoperatively, the patient showed clinical improvement with resolution of pain, absence of systemic signs of infection, and satisfactory wound healing. Conclusion: Gangrene complicated by osteomyelitis requires comprehensive evaluation and prompt management. Timely minor amputation combined with adequate debridement and infection control can serve as an effective definitive treatment to eradicate the source of infection and promote wound healing.   Keywords: Chronic Wound; Gangrene; Lower Extremity Infection; Minor Amputation; Osteomyelitis.